Extraction Method of Ultrasound-Assisted Extraction (UAE) of Robusta Coffee Skin Waste using 96% Ethanol Solution in Tanah Wulan Village, Maesan District, Bondowoso Regency - Miftakhul Ulum; Fitriah Novita Sari; Helda Wika Amini; Hanggara Sudrajat (Program Studi Teknik Kimia Universitas Jember, 2022)
Argopuro Mountains, Tanah Wulan Village, Maesan District, Bondowoso Regency, East Java, Indonesia is one of the Robusta coffee-producing areas. Robusta coffee beans that are processed can produce quite a lot of by-products in the form of underutilized waste. It is known that coffee skin waste still has a lot of remaining content and it is possible to take these bioactive compounds using extraction methods. Bioactive compounds in natural materials can be done by extraction. Extraction is the process of separating substances in a sample based on different solubilities. The extraction method used is the ultrasonication method (nonconventional). Extraction of the ultrasonication method only requires a relatively shorter time with the help of an ultrasonicator. There is a lot of content in the coffee skin waste powder that needs further testing. The results of this study are expected to provide economic value to robusta coffee husk waste.